Antenatal yoga relaxation and exercise in pregnancy - Robinson, Tricia; Gammond, Julian; Gammond, Stephen; Green Umbrella ([United Kingdom] : Green Umbrella Productions, 1991)
This easy to follow beginner's guide to yoga during pregnancy not only features safe yoga exercises, but also offers relaxation tips, helpful breathing techniques and labour and birth positions for the expectant mother
Title from title screen
Narrated by kathy Tayler
Yoga consultant: Maria Bailey
DVD format
Keywords: Hatha yoga; Yoga; Exercise for pregnant women